Varying the ionic functionalities of conjugated polyelectrolytes leads to both p- and n-type carbon nanotube composites for flexible thermoelectrics1. Issue 8 (29th August 2015) - Mai, Cheng-Kang; Russ, Boris; Fronk, Stephanie L.; Hu, Nan; Chan-Park, Mary B.; Urban, Jeffrey J.; Segalman, Rachel A.; Chabinyc, Michael L.; Bazan, Guillermo C.
<x xml:space="preserve">Abstract</x> Selective doping of single-walled carbon nanotubes can be achieved by varying pendant ionic functionalities of conjugated polyelectrolytes.